“Model Pelembagaan Program One Village One Product ( OVOP ) dalam Upaya Pemberdayaan Ekonomi Masyarakat melalui Pengembangan Tenun Troso di Kabupaten Jepara” - Rahmah Wijayanti; Fathurrochman Fathurrochman (Journal of Public Policy and Management Review, 2016)
Indonesia as an archipelagic nation has the characteristics of the area was well as the condition of heterogeneous society. It causes implemented of generalized policies in each area is not a good strategy and it makes regional disparities. Population density and the labor was increase that isn’t balance with the jobs cause the special problem. So there is a program based development empowerment that make local potential is optimal. It applied in some government program. One way to applied is the One Village One Product (OVOP) program. It can be expected to make the people can stand alone in each way. Jepara is the area that success applied this program in Tenun Troso way. The purpose of this study is to determine the process of implementation of One Village One Product and explore things that make OVOP program Tenun Troso in Jepara success . It can build empowerment model that used in the implementation of OVOP program in Jepara that can be a sample for the other areas. This study uses qualitative descriptive method using a grand theory and the theory of the institutional system and three way fit theory David Korten as midle theory. The result of this study found many factors that make the program success in an inverse system model . the ideas, programs , and resources can be applied in the organization , that doctrine from the leader and the full support from the acceptor make prosperity is increase. it is very influential for the next program improvement .